(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
If the Intertextuality of the modern criticism terms, the phenomenon Intertextuality has its origins in ancient Arabic literature, that the ancient critics called it other names, one of the importants; the imitation, from here this research sheds light on Al – Hamawi’s Lamiya of the Prophetic Praise, as an imitation for two poems together are; Al – Boussiri, and Kaib ibn Zohier’s Lamiyas, especially that the art of Prophetic Praise has flourished in the Mamluky era from one side, and this era is one of the most productive eras of Arabic Literature production of poetic imitation from the other side. This research found that is Prophetic Praise poems is characterized by predominantly religious, if that was on the technical side, it was shown with a high degree of interference between two Lamiyas Al – Hamawi and Al – Boussiri; in particular that elements of the Prophetic Praise poems and the many poetic imitation made it take fixed template as well.